1964
DOI: 10.1083/jcb.22.2.365
|View full text |Cite
|
Sign up to set email alerts
|

Wound Healing and Collagen Formation

Abstract: The changes in scorbutic wounds following the administration of ascorbic acid have been investigated using the techniques of electron microscopy, histochemistry, and autoradioggraphy. Particular attention has been paid to the changes seen in the endoplasmic reticulum of the fibroblasts and to the identity of the extracellular filamentous material characteristic of scorbutic wounds. Seven-day-old wounds in scorbutic guinea pigs were examined prior to and from one to 72 hours following the administration of vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
27
0

Year Published

1964
1964
1999
1999

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(35 citation statements)
references
References 35 publications
8
27
0
Order By: Relevance
“…A small but significant amount of underhydroxylated collagen has been found in connective tissue from scorbutic guinea pigs, and the results are consistent with the suggestion that scurvy produces an intracellular accumulation of severely underhydroxylated collagen which may after a time inhibit further synthesis of protocollagen (Barnes et al, 1970). Such a build-up might give rise to the distortion of the endoplasmic reticulum and changes in ribosomal patterns seen in electronmicroscopic studies of scorbutic guinea-pig wounds (Ross & Benditt, 1964). However, these disturbances of the cellular apparatus for protein synthesis are rapidly restored to the normal conformation when ascorbic acid is administered to the scorbutic animal and a concomitant appearance of extracellular collagen fibres is observed in the wound tissue (Ross & Benditt, 1964).…”
supporting
confidence: 76%
“…A small but significant amount of underhydroxylated collagen has been found in connective tissue from scorbutic guinea pigs, and the results are consistent with the suggestion that scurvy produces an intracellular accumulation of severely underhydroxylated collagen which may after a time inhibit further synthesis of protocollagen (Barnes et al, 1970). Such a build-up might give rise to the distortion of the endoplasmic reticulum and changes in ribosomal patterns seen in electronmicroscopic studies of scorbutic guinea-pig wounds (Ross & Benditt, 1964). However, these disturbances of the cellular apparatus for protein synthesis are rapidly restored to the normal conformation when ascorbic acid is administered to the scorbutic animal and a concomitant appearance of extracellular collagen fibres is observed in the wound tissue (Ross & Benditt, 1964).…”
supporting
confidence: 76%
“…The appearance of the fibroblasts concomitant with the decrease in collagen in diabetic wounds suggested that the fibroblasts were not responding to injury as observed in control hamsters, but instead were undergoing progressive degeneration. This has been confirmed in other studies where the fibroblast was compromised and unable to synthesise collagen [23][24][25] and from reports examining the activity of fibroblasts in vitro from diabetic patients [26]. In every instance there was a n impaired response to injury with decreased collagen synthesis in vivo and in vitro and shorter life span in vitro [27].…”
Section: Discussionsupporting
confidence: 72%
“…14). These sites were pointed out also in an earlier study of wounds (21), as well as by Karrer (28) in studies of the developing chick embryo aorta. Although frequent, these areas are not seen in every cell in each micrograph.…”
Section: Figure 10mentioning
confidence: 75%
“…4 and 5). Ribosomes appeared to be labeled in regions where tangential sections of the membranes of the ergastoplasm demonstrate the characteristic aggregates of ribosomes (21) (Figs. 5 and 6).…”
Section: Endoplasmic Reticulum Fifteen Minutes Aftermentioning
confidence: 99%